Systematic review of interventions for treating or preventing antipsychotic-induced tardive dyskinesia - Bergman, Hanna; Walker, Dawn-Marie; Nikolakopoulou, Adriani; Soares-Weiser, Karla; Adams, Clive E. (NIHR Health Technology Assessment Programme, 2017)
Background: Antipsychotic medication can cause tardive dyskinesia (TD) – late-onset, involuntary, repetitive movements, often involving the face and tongue. TD occurs in > 20% of adults taking antipsychotic medication (first-generation antipsychotics for > 3 months), with this proportion increasing by 5% per year among those who continue to use these drugs. The incidence of TD among those taking newer antipsychotics is not different from the rate in people who have used older-generation drugs in moderate doses. Studies of TD have previously been found to be limited, with no treatment approach shown to be effective. Objectives: To summarise the clinical effectiveness and safety of treatments for TD by updating past Cochrane reviews with new evidence and improved methods; to undertake public consultation to gauge the importance of the topic for people living with TD/the risk of TD; and to make available all data from relevant trials. Data sources: All relevant randomised controlled trials (RCTs) and observational studies. Review methods: Cochrane review methods, network meta-analysis (NMA). Design: Systematic reviews, patient and public involvement consultation and NMA. Setting: Any setting, inpatient or outpatient. Participants: For systematic reviews, adults with TD who have been taking a stable antipsychotic drug dose for > 3 months. Interventions: Any, with emphasis on those relevant to UK NHS practice. Main outcome measures: Any measure of TD, global assessments and adverse effects/events. Results: We included 112 studies (nine Cochrane reviews). Overall, risk of bias showed little sign of improvement over two decades. Taking the outcome of ‘TD symptoms improved to a clinically important extent’, we identified two trials investigating reduction of antipsychotic dose [n = 17, risk ratio (RR) 0.42, 95% confidence interval (CI) 0.17 to 1.04; very low quality]. Switching was investigated twice in trials that could not be combined (switching to risperidone vs. antipsychotic withdrawal: one RCT, n = 42, RR 0.45, 95% CI 0.23 to 0.89; low quality; switching to quetiapine vs. haloperidol: one RCT, n = 45, RR 0.80, 95% CI 0.52 to 1.22; low quality). In addition to RCTs, six observational studies compared antipsychotic discontinuation with decreased or increased dosage, and there was no clear evidence that any of these strategies had a beneficial effect on TD symptoms (very low-quality evidence). We evaluated the addition to standard antipsychotic care of several treatments, but not anticholinergic treatments, for which we identified no trials. We found no clear effect of the addition of either benzodiazepines (two RCTs, n = 32, RR 1.12, 95% CI 0.6 to 2.09; very low quality) or vitamin E (six RCTs, n = 264, RR 0.95, 95% CI 0.89 to 1.01; low quality). Buspirone as an adjunctive treatment did have some effect in one small study (n = 42, RR 0.53, 95% CI 0.33 to 0.84; low quality), as did hypnosis and relaxation (one RCT, n = 15, RR 0.45, 95% CI 0.21 to 0.94; very low quality). We identified no studies focusing on TD in people with dementia. The NMA model found indirect estimates to be imprecise and failed to produce useful summaries on relative effects of interventions or interpretable results for decision-making. Consultation with people with/at risk of TD highlighted that management of TD remains a concern, and found that people are deeply disappointed at the length of time it has taken researchers to address the issue. Limitations: Most studies remain small and poorly reported. Conclusions: Clinicians, policy-makers and people with/at risk of TD are little better informed than they were decades ago. Underpowered trials of limited quality repeatedly fail to provide answers. Future work: TD reviews have data from current trials extracted, tabulated and traceable to source. The NMA highlights one context in which support for this technique is ill advised. All relevant trials, even if not primarily addressing the issue of TD, should report appropriate binary outcomes on groups of people with this problem. Randomised trials of treatments for people with established TD are indicated. These should be large (> 800 participants), necessitating accrual through accurate local/national registers, including an intervention with acceptable treatments and recording outcomes used in clinical practice. Study registration: This study is registered as PROSPERO CRD4201502045. Funding: The National Institute for Health Research Health Technology Assessment programme.